Penggunaan Ungkapan Sumimasen Bahasa Jepang dan Nuwun Sewu Bahasa Jawa Dalam Kalimat Permohonan (Kajian Analisis Kontrastif) - Sony Difa Febrianda; Indrowaty, Sri Aju (AYUMI : Jurnal Budaya, Bahasa dan Sastra, 2025)
This study compares the Japanese expression sumimasen and the Javanese expression nuwun sewu, both of which function as forms of apology or request, through a contrastive analysis approach. The focus of this research is to identify the similarities and differences in terms of usage context, pragmatic meaning, and the implicit as well as explicit cultural values embedded in these expressions. The study aims to understand the linguistic and cultural dynamics that influence the use of both expressions. Data were collected from various written sources relevant to these expressions. The method employed in this study is descriptive qualitative. The findings indicate that sumimasen and nuwun sewu are both used in contexts of apology or request; however, they differ significantly in terms of politeness levels, social contexts, and cultural backgrounds. Sumimasen tends to be used in both formal and informal situations with an emphasis on general politeness, whereas nuwun sewu is more commonly found in Javanese culture, which emphasizes social hierarchy and the concept of unggah-ungguh (etiquette or respectful behavior). The results of this study are expected to contribute to cross-cultural studies, particularly in understanding the pragmatic differences between Japanese and Javanese in the context of making requests or apologies. Keywords: Contrastive Analys